Analisis Perbandingan Biaya dan Penggunaan Obat Antara Pasien BPJS Kesehatan dan Non-BPJS Kesehatan Periode Januari-Desember 2022 di Klinik Pratama X Kota Bandung - Wilis, Phebe Ariella; Padmasawitri, Tjokorde Istri Armina; Qanaah, Syifa Fitrah (Jurnal Ekonomi Kesehatan Indonesia, 2025)
Primary healthcare facilities may have two sources of drug funding: capitation funds for drugs prescribed to patients under the Social Security Administering Agency (BPJS Kesehatan), and out-of-pocket payments from non-BPJS Kesehatan patients. Analyzing drug utilization patterns and financing is essential to ensure the efficient use of these funding sources. This study aims to analyze drug costs and utilization among BPJS Kesehatan patients compared to non-BPJS Kesehatan patients at Primary Clinic X in Bandung City from January to December 2022.This study used a retrospective cross-sectional design with data collected from electronic medical records and pharmacy transactions. Descriptive analysis was employed to compare the number and cost of prescriptions. In contrast, inferential analysis (t-test and ANOVA) was used to assess differences in drug costs across patient occupational groups. Of 6,846 patients, 1,964 were BPJS Kesehatan participants and 4,882 were non-BPJS Kesehatan patients. More drugs were prescribed to non-BPJS Kesehatan patients, but the average cost per prescription was higher among BPJS Kesehatan patients (Rp37,424.23 vs. Rp 32,341.87; p= 0.003). The average monthly proportion of capitation funds used for drugs was 27.89%. The retiree group had the highest average prescription cost (Rp56,337), while students had the lowest (Rp28,078), with significant differences among occupational categories (p< 0.05). At the study site, the average drug cost for BPJS Kesehatan patients was higher than for non-BPJS Kesehatan patients due to the dominance of elderly patients with chronic diseases. These findings highlight the impact of an aging population and rising chronic disease prevalence on increased drug costs, which pose a challenge for capitation fund management.